A novel sodium-fluorescent crystal - Yunsu Ma; Yongjie Liu; Yuan Wang; Fan Zhang; Dongzhi Yang (Royal Society Open Science, 2021)
In this work, a novel sodium-fluorescent crystal (Na-FS) was synthesized from 4-dimethylaminobenzoic acid and sodium hydroxide by one-pot hydrothermal method. The structure and conformation of Na-FS were confirmed by single-crystal X-ray diffraction and scanning electron microscope, and the optical properties were studied by fluorescence spectrometer. The results showed that: Na-FS was a triclinic crystal, space group was P-1, cell parameters a, b and c were 10.5113(3), 15.9198(5) and 15.9560(5) Å, respectively, and the number of independent atoms Z in a structure cell was two. Additionally, Na-FS has a blue fluorescence emission (around 360 nm under excited at the range of 230–300 nm) with great photostability and photobleaching resistance, and the quantum yield of Na-FS is 30.58%.